Seasonal occurrence and offshore accumulation of phycotoxins in a subtropical semi-enclosed bay: Insights from a year-round survey in Qinzhou Bay, South China Sea - Hui-Xia Geng; Zhuo-Ru Lin; Wen-Jiao Tang; Sara A. Cunha; Zhen-Jun Kang; Xiao-Tian Han; Jin-Xiu Wang; Ren-Cheng Yu (Marine Pollution Bulletin, 2026)

Paternal vitamin D deficiency is associated with offspring testicular developmental abnormalities, fibrosis, and altered sperm miRNA profiles - Yu-Ming Chen; Zhi-Hong Tian; Shi-Yuan Li; Juan Dai; Xing-Ru Wang; Guo-Ying Sun; Min Liu; Berthold Hocher; Mei Tian (Molecular Biology Reports, 2026)

A novel inversion method for assessing pipe corrosion condition based on upstream-downstream water quality variation in drinking water distribution systems - Yun-Qiao Zeng; Tian-Yang Zhang; Zhen-Ning Luo; Ling Hu; Bing Geng; Renjie Pan; Zhu Peng; Dai-Xu Zhang; Yi-Ru Chen; Huan He; Mohamed Gamal El-Din; Bin Xu (Water Research, 2026)

Colloidal biochar promotes microbial carbon dioxide fixation and enhances net soil organic carbon gain - Jia Bing Liu; Jia Wang; Wang Kai Tong; Han Tang; Mei Ru Yue; Piao Yi Jiang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2026)

Mixed-gas nanobubble and colloidization stacked modification: Enhancing porous/chemical properties and endowing rapid adsorption function of biochar - Mei Ru Yue; Han Tang; Wang Kai Tong; Jia Bing Liu; Piao Yi Jiang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2026)

Pickering emulsion stabilized by whey protein isolate and psyllium husk powder: Interface properties and stabilization mechanism - Huifang Liu; Ru Tian; Yinshi Sun; Shuang Jiang; Di Qu (Food Chemistry, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Divergent responses of soil respiration to reduced rainfall amount and frequency, and to nitrogen fertilization in a typical steppe - Lan Du; Yan Shen; Jiatao Zhang; Yonghong Luo; Jinbao Zhang; Ru Tian; Zhuwen Xu (Journal of Environmental Management, 2026)

Elucidating the role of ammonia doping in modulating combustion dynamics in ethane fuel-rich jet flames - Bipro Gain; Muhammad Bilal; Yun-Fan Wang; Ahmed E. Mansy; Muhammad Yousuf; Kai-Ru Jin; Du Wang; Boyang Su; Aqsa Liaqat; Mohammed Khalil; Zhi-Min Wang; Qingli Li; et al. (Fuel, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Bioactive PVA/SDES propolis extracts composite films for extending oyster shelf life: Structure, functionality, and preservation performance - Tian Du; Lin-Kun Sun; Pei-Ru Zhou; Yu-Cang Zhang; Yan-Zhen Zheng (Food Packaging and Shelf Life, 2026)

Influence of climate change on suitable areas for three Salvia species and their pollinators - Feng-Shi Zhang; Han-Wen Xiao; Ru-Nan Tian (Plant Ecology, 2026)

Synergistic flavor enhancement and polycyclic aromatic hydrocarbons inhibition in roasted fish by Perilla-clam/yeast composite extracts: Regulation of Maillard reaction and lipid oxidation pathways - Yiling Tian; Tong Li; Yunyue Shan; Shanbai Xiong; Ru Liu; Yueqi An (Food Chemistry, 2026)

Multi-system geochronometer constraints on thermo-tectonic evolution of the Qiangtang Terrane, central Tibetan Plateau: Comment - Xiao-Long Song; Ru-Ye Tian; Kang-Yu Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

Mechanism of flavor enhancement by yeast extract and clam extract in ginger-surimi cake: Insights from flavoromics and machine learning - Yiling Tian; Hanpu Gao; Tong Li; Yunyue Shan; Shanbai Xiong; Ru Liu; Yueqi An (Food Research International, 2026)

Influence of extraction conditions on self-assembled colloidal particle formation in ginseng aqueous extract - Di Qu; Ru Tian; Huifang Liu; Jiyue Sha; Zhitong Wang; Liankui Wen (Food Chemistry, 2026)

Microbial functional shifts drive soil phosphorus transformation under long-term nitrogen and water inputs in a semi-arid grassland - Mohsin Mahmood; Ru Tian; Yan Shen; Jiatao Zhang; Lan Du; Anam Ayyoub; Ansa Rebi; Adnan Mustafa; Haoyue Chen; Yiming Zhao; Wenhuai Li; Le Qi; et al. (CATENA, 2026)

Near-full-component sewage sludge valorization via integrated alkali-mediated pyrolysis and sub-boiling temperature crystallization of hierarchical carbon-zeolite composites from carbonaceous and inorganic constituents - Zhihang Yuan; Houmin Yin; Jicui Cui; Changfu Yang; Zhou Zhen; Xiaohan Cui; Yumeng Jin; Lifeng Lin; Long Kong; Ruina Zhang; Ruyi Wang; Lei Che; et al. (Water Research, 2026)

Mechanistic link between eIF4E phosphorylation and viral pathogenesis: Therapeutic insights from a porcine model - Wen-Jun Tian; Yan-Ru Zhang; Jing-Ling You; Xiao-Jie Wu; Xiao-Fang Hu; Xiao-Jia Wang (Veterinary Microbiology, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Sustainable extraction and bioconversion of tea stems using NADES: Dual benefits in polyphenolic recovery and carbohydrates enzymatic hydrolysis - Lin-Kun Sun; Pei-Ru Zhou; Tian Du; Yu-Cang Zhang; Yan-Zhen Zheng (Food Chemistry, 2026)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Mixed gas nanobubbles promote microbial CO2 fixation: Universal verification, mechanism, and application - Jia Wang; Piao Yi Jiang; Jia Bing Liu; Han Tang; Wang Kai Tong; Jia Jie Zou; Mei Ru Yue; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2025)

Soot characterization of n-dodecane combustion in multi-jet premixed flames: A multi-scale analysis - Xiao-Hong Gui; Jiao-Jiao Wu; Wen-Jun Zhou; Ling-Nan Wu; Kai-Ru Jin; Wen-Jiao Wang; Zhen-Yu Tian (Fuel, 2025)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

A Transformer-based framework with generative spectral augmentation for online monitoring of hyaluronic acid fermentation - Weilu Tian; Lixuan Zang; Yunyi Li; Cheng Peng; Jinhua Zhang; Huarong Shao; Ruiqing Xian; Ru Sun; Fei Liu; Haining Tan; Peixue Ling (Carbohydrate Polymers, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Low-intensity pulsed ultrasound promotes proliferation and differentiation of neural stem cells to enhance spinal cord injury recovery - Ye-Hui Liao; Min-Hao Tian; Wen-Yang Zhou; Bao-Qiang He; Chao Tang; Qiang Tang; Ru-Pei Ye; De-Jun Zhong (Molecular Biology Reports, 2025)

Nitrogen enrichment offsets the stimulation of soil respiration by increased precipitation in temperate grasslands - Ru Tian; Jiatao Zhang; Yan Shen; Lan Du; Jinbao Zhang; Shijia Yang; Zhongxiang Liu; Mengle Wang; Zhuwen Xu (Agricultural and Forest Meteorology, 2025)

Boosting brains: exercise enhances cognition and neurone density in a fish reared for release into nature - Yimeng Wang; Mengjia Tian; Haoyu Guo; Joacim Näslund; Yucheng Wang; Jiangfeng Ru; Yulu Qi; Kuo Tian (Animal Behaviour, 2025)

Enhancing soil carbon sequestration capacity: Synergistic effect of low-release biochar and autotrophic microbial agents over one year - Han Tang; Jiajun Hu; Yundong Liu; Bu Li; Jia Wang; Wang Kai Tong; Mei Ru Yue; Jia Jie Zou; Min-tian Gao; Saiwei Zhang; Nan Liu; Jixiang Li (Journal of Environmental Chemical Engineering, 2025)

Reprocessable cross-linked EPDM elastomers with dynamic and tuneable imine network based on electronic effect - Zhongyang Liu; Ming Cao; Haoran Liu; Bin Wu; Jibin Miao; Youfeng Tian; Yuchao Ke; Ru Xia; Jiasheng Qian (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Insight into the effect of ammonia doping on the methane jet flame - Bipro Gain; Muhammad Bilal; Yun-Fan Wang; Samuel Daniel; Wang Du; Ahmed E. Mansy; Kai-Ru Jin; Zhen-Yu Tian (Fuel, 2025)

Multispectral analysis and molecular docking simulation of the inhibition mechanism of dietary anthocyanins on acetylcholinesterase - Nuo Wang; Min Zhao; Yue Li; Hao-Yu Xue; Xu Si; Chi Shu; Ying Zhou; Bao-Ru Yang; Sergey S. Makarov; Anton I. Chudetsky; Liang Wang; Ying He; et al. (Food Bioscience, 2025)

Electrocatalytic synergistic degradation of tetracycline by low-energy-consumption Mn0.22-NiS nanosheet electrodes: Interface mechanism and toxicity analysis - Fan-Hao Hu; Qun-Feng Ye; Si-Ru Chen; Ya-Wen Yu; Hao Chen; Su-Fang Qin; Le-Xing You; Xiao-Chun Tian; Feng Zhao (Chemical Engineering Journal, 2025)

A dual model-based evolutionary framework for dynamic large-scale sparse multiobjective optimization - Panpan Zhang; Ru Zhang; Ye Tian; Kay Chen Tan; Xingyi Zhang (Swarm and Evolutionary Computation, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Improved antifouling and regeneration capability of polyaniline-modified halloysite nanotube/MXene composite membranes - Jing-Yi Feng; Wen-Hao Geng; Ru-Yu Chang; Yu-Han Wang; Yue-Xin Wang; Ze-Long Bao; Wen-Yi Sun; Lu-Yao Tian; Di Zhang; Hong-Zhang Geng (Journal of Water Process Engineering, 2025)

Factors affecting seed germination in critically endangered Salvia daiguii: Seed quality, temperature and light, osmotic potential, pH, hand pollination, hormones, and mucilage - Han-Wen Xiao; Ruo-Qing Jiang; Yan-Bo Huang; Ru-Nan Tian (Journal for Nature Conservation, 2025)

Systematic review of natural coumarins in plants (2019–2024): Chemical structures and pharmacological activities - Ze-Dong Nan; Ying Shang; Yi-Dong Zhu; Hui Zhang; Ru-Ru Sun; Jing-Jing Tian; Zhi-Bo Jiang; Xiao-Li Ma; Changcai Bai (Phytochemistry, 2025)

Comprehensive molecular biology and metabolomics analysis reveal the changes on muscle quality of Megalobrama amblycephala exposure to ammonia nitrogen during transportation - Ling Peng; Ziaur Rahman; Yuanyong Tian; Tao Yin; Shanbai Xiong; Juan You; Ru Liu; Lan Wang; Qilin Huang; Huawei Ma (Food Research International, 2025)

Schiff base crosslinking based dialdehyde-chitosan/gelatin/tea polyphenol electrospun nanofibrous membranes with excellent antibacterial and antioxidant activity for food packaging - Yu Ma; Ru Tian; Yudong Song; Mengxiao Liu; Jie Li; Zhichun Bi; Hui Huang; Yongxin Li (Food Packaging and Shelf Life, 2025)

Degradation-Resistant Biochar Improves Soil Organic Carbon Storage: Promoting Autotrophic Metabolism & Increasing Refractory Organic Carbon - Han Tang; Jiajun Hu; Bu Li; Yundong Liu; Wang Kai Tong; Mei Ru Yue; Jia Wang; Wenjuan Wang; Min-tian Gao; Nan Liu; Jixiang Li (Bioresource Technology, 2025)

Surface and interface modification of biochar based on thermal nanobubble water - Mei Ru Yue; Jia Bing Liu; Piao Yi Jiang; Wang Kai Tong; Han Tang; Jia Wang; Wenjuan Wang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Optimizing boron oxide-support interactions for enhanced catalytic stability in propane oxidative dehydrogenation - Jinshu Tian; Kerou Hu; Ling Fang; Chi Wang; Ru Kong; Mingwu Tan; Lili Zhang; Zhongting Hu; Xiaonian Li; Yihan Zhu (Chemical Engineering Journal, 2025)

Functional analysis of Ophraella communa Lesage OcomOBP11 in recognition of Ambrosia artemisiifolia L. volatiles - Yang Yue; Chao Ma; Yan Zhang; Wei-hua Ma; Jing-jing Wang; Zhen-ya Tian; Guang-mei Chen; Ru-wen Li; Jin-hua Li; Jing-fang Yang; Zhong-shi Zhou (Pesticide Biochemistry and Physiology, 2025)

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Electrospun nanofiber membranes based on dialdehyde pullulan polysaccharide and schiff base crosslinked lysozyme for antibacterial packaging of blueberries - Yu Ma; Ru Tian; Yudong Song; Chenghui Yin; Hui Huang; Yongxin Li (Food Bioscience, 2025)

Interface selectivity-based biochar: Directional evolution of properties, application & carbon neutralization evaluation - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Mei Ru Yue; Yun Dong Liu; Bu Li; Jia Jie Zou; Jia Wang; Han Tang; Min-tian Gao; Yucang Liang; Wenjuan Wang; et al. (Chemical Engineering Journal, 2025)

Enzymatic degradation of Ochratoxin A by a novel bacterium, Microbacterium esteraromaticum ASAG1016 - Ru Jia; Jingyi Zhao; Senmiao Tian; Faizan Ahmed Sadiq; Simeng Lu; Pengyan Gao; Guohua Zhang (International Journal of Food Microbiology, 2025)

Dissimilatory nitrate reduction to ammonium driven by different electron donors: Mechanisms, recent advances, and future perspectives - Wan-Ru Wen; Tian-Chen Liu; Sheng-Qiang Fan; Xin Tan; Yang Lu; De-Feng Xing; Bing-Feng Liu; Nan-Qi Ren; Guo-Jun Xie (Chemical Engineering Journal, 2025)

Toxicokinetics and reproductive toxicity of maternal bisphenol AF exposure during gestation in offspring of Sprague Dawley rats - Yaxuan Zhu; Xiuxiang Liu; Xiuying Liu; Yijiao Shi; Huaxin Li; Shaoguo Ru; Hua Tian (Chemico-Biological Interactions, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Differentiation revelation of wine quality induced by maceration technology under the mediation of environmental factors and microbial community - Manman Gao; Shuo Yu; Jianing Bai; Ru Chen; Yunjie Li; Liping Du; Lijuan Ma; Huiling Zhang; Xiaoju Tian (Food Bioscience, 2025)

Rapid and visual detection of the strawberries pathogenic fungi Fusarium oxysporum and Colletotrichum siamense by one-pot LAMP-CRISPR/Cas12b - Ya-Ru Tian; Dong-Lan Tang; Tian-Qi Wang; Jia-Yue Chen; Yan-Fang Dong; Xin-Yu Ying; Dan Zhang; Wen-Jing Wang; Zhi-Dan Luo (Journal of Plant Diseases and Protection, 2025)

Global surface eddy mixing ellipses: spatio-temporal variability and machine learning prediction - Tian Jing; Ru Chen; Chuanyu Liu; Chunhua Qiu; Cuicui Zhang; Mei Hong (Frontiers in Marine Science, 2025)
Mesoscale eddy mixing significantly influences ocean circulation and climate system. Coarse-resolution climate models are sensitive to the specification of eddy diffusivity tensor. Mixing ellipses, derived from eddy diffusivity tensor, illustrate mixing geometry, i.e., the magnitude, anisotropy, and dominant direction of eddy mixing. Using satellite altimetry data and the Lagrangian single-particle method, we estimate eddy mixing ellipses across the global surface ocean, revealing substantial spatio-temporal variability. Notably, large mixing ellipses predominantly occur in eddy-rich and energetic ocean regions. We also assessed the predictability of global mixing ellipses using machine learning algorithms, including Spatial Transformer Networks (STN), Convolutional Neural Network (CNN) and Random Forest (RF), with mean-flow and eddy- properties as features. All three models effectively represent and predict spatiotemporal variations, with the STN model, which incorporates an adaptive spatial attention mechanism, outperforming RF and CNN models in predicting mixing anisotropy. Feature importance rankings indicate that eddy velocity magnitude and eddy size are the most significant factors in predicting the major axis and anisotropy. Furthermore, training the models with a 2-year temporal duration, aligned with the El Niño Southern Oscillation (ENSO) timescale, improved predictions in the northern equatorial central Pacific region compared to models trained with a 12-year duration. This resulted in a spatially averaged correlation increase of over 0.5 for predicting the minor axis and anisotropy, along with a reduction of more than 0.15 in the Normalized Root Mean Square Error. These findings highlight the considerable potential of machine learning algorithms in predicting mixing ellipses and parameterizing eddy mixing processes within climate models.

Integrative models for environmental forecasting of phthalate migration from microplastics in aquaculture environments - Shan Zhong; Ruiyue Li; Yaowen Tian; Zengxian Wei; Lishan Zhang; Yan Chen; Ruyue Zhou; Qian Zhang; Xuan Ru (Journal of Hazardous Materials, 2024)

Comparative analysis of the fatty acid profiles in goat milk during different lactation periods and their interactions with volatile compounds and metabolites - Guang-qin Liao; Hao-lei Han; Tian-cai Wang; Hou-ru Li; Yong-zhong Qian; Mai-xun Zhu; Qi Jia; Jing Qiu (Food Chemistry, 2024)

Nitrogen addition alleviates the negative effects of reduction in precipitation on soil multifunctionality in a typical steppe - Yan Shen; Yonghong Luo; Lan Du; Ru Tian; Wenqian Shao; Jiatao Zhang; Na Li; Jinbao Zhang; Shan Wang; Mohsin Mahmood; Zhuwen Xu (Applied Soil Ecology, 2024)

Classification method of infrasound events based on the MVIDA algorithm and MS-SE-ResNet - Xiao-Feng Tan; Xi-Hai Li; Chao Niu; Xiao-Niu Zeng; Hong-Ru Li; Tian-You Liu (Applied Geophysics, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Response of anammox to organics with different degradation characteristics and exposure time: Performance, sludge characteristics and bacterial community - Shuai Zhang; Long-Yun Lai; Tian-Xiang Wang; Wei-Lei Jin; Ru-Ru Yi; Dong-Zhi Chen; Ren-cun Jin; Guang-feng Yang (Science of The Total Environment, 2024)

An embryonic intra-oceanic subduction in the Bangong−Nujiang Meso-Tethys: insights from Late Jurassic Nd Hf isotopic decoupling adakitic granodiorites in the Dongco ophiolite of central Tibet - Xin-Miao Wang; Chen Ji; Kai-Jun Zhang; Ru-Ye Tian; Kang-Yu Li (Lithos, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Geranylgeraniol: Bio-based platform for teprenone, menaquinone-4, and α-tocotrienol synthesis - Haoming Chi; Shun Wen; Tian Wen; Liying Er; Ru Lei; Chong Dai; Guangkai Bian; Kun Shen; Tiangang Liu (Bioresource Technology, 2024)

Ubiquity and ecological risks of conjugated steroids cannot be overlooked: First evidence from estuarine sediments - Fei Tian; Shan Liu; Ru Xu; Nian-Nian Wu; Shuang-Shuang Liu; Yuan-Yue Cheng; Qian Xiong; Zhen-Zhao Tang; Lin-Bao Zhang; Zhe Zhang; Hai-Gang Chen (Marine Pollution Bulletin, 2024)

Prenatal exposure to bisphenol AF causes toxicities in liver, spleen, and kidney tissues of SD rats - Yaxuan Zhu; Xiuxiang Liu; Yijiao Shi; Xiuying Liu; Huaxin Li; Shaoguo Ru; Hua Tian (Food and Chemical Toxicology, 2024)

Promoting symbiotic relationship between microalgae and bacteria in wastewater treatment processes: Technic comparison, microbial analysis, and future perspectives - Cong-Cong Tang; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2024)

The cooperative p-n heterojunction and Schottky junction in Au-decorated hierarchical CuS@SnS2 hollow cubes for boosted charge transport and CO2 photoreduction - Yuejia Yin; Yajie Chen; Xinyan Yu; Qiuyu Zhang; Yaxin Ru; Guohui Tian (Chemical Engineering Journal, 2024)

Drought and nitrogen deposition regulate plant nutrient resorption in a typical steppe - Yonghong Luo; Yan Shen; Ahmed Salah Elrys; Lan Du; Mohsin Mahmood; Jiatao Zhang; Haiyan Ren; Jinbao Zhang; Na Li; Ru Tian; Wenqian Shao; Ahmed S.M. Elnahal; et al. (Agriculture, Ecosystems & Environment, 2024)

Ecological restoration largely alleviates livestock grazing pressure in a montane grassland - Xiao-lian Qi; Hao-jie Xu; Ru-yu Teng; Tian Chen; Xu-dong Wang (Journal of Cleaner Production, 2024)

Spatially confined conjugation of enzyme immobilized magnetic nanochains with poly(vinylphosphonic acid) polymers using droplet reactors for uranium extraction - Danqing Shen; Qian Du; Pan Wang; Xiaohua Tian; Yue Wang; Ru Feng; Jianming Pan (Chemical Engineering Journal, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Identification and functional analyses of CD4-1+ cells in grass carp (Ctenopharyngodon idella) - Xue-Qing Han; Yi-Ru Pan; Ya-Qin Zhong; Tian-Tian Tian; Xun Liu; Xu-Jie Zhang; Yong-An Zhang (Fish & Shellfish Immunology, 2024)

Effects of exercise training on the external morphology, growth performance, swimming ability, body composition and metabolism of juvenile black seabream Acanthopagrus schlegelii - Haoyu Guo; Jinbo Zhai; Mengjia Tian; Joacim Näslund; Jiangfeng Ru; Yingying Ou; Yulu Qi; Qingsong Hu; Kai Liu; Xiumei Zhang (Aquaculture, 2024)

Reduction in precipitation amount, precipitation events, and nitrogen addition change ecosystem carbon fluxes differently in a semi-arid grassland - Lan Du; Yonghong Luo; Jiatao Zhang; Yan Shen; Jinbao Zhang; Ru Tian; Wenqian Shao; Zhuwen Xu (Science of The Total Environment, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Initiation and Propagation of Interface Cracks in Layered Composite Rocks: An Investigation Using True Triaxial Experiments - Jian-Zhi Zhang; Tian-Tian Gu; Ru-Fang Zhan; Zhao-Peng Zhang (Geotechnical and Geological Engineering, 2024)

Dissolved oxygen and ammonia affect ammonia production via GDH/AMPK signaling pathway and alter flesh quality in Chinese perch (Siniperca chuatsi) - Ru Yang; Xuange Liu; Yong Liu; Qingda Tian; Ziwei Wang; Dejie Zhu; Zhisong Qian; Yi Yi; Jiacheng Hu; Yan Li; Xu-Fang Liang; Liwei Liu; et al. (Fish Physiology and Biochemistry, 2024)

A clean label O/W pickering emulsion stabilized by pectin-containing lignocellulosic nanofibrils isolated from apple pomace - Chi Zhang; Tian Gong; Shan Qiang; Xiao Yu Wang; Xiao Ru Wang; Shuai Zhang; Yong Hong Meng (Food Hydrocolloids, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

Comparative evaluation of acid-resistant nanofiltration membranes for heavy metal removal in acidic wastewater - Chun Cui; Cong Luo; Tian Tian; Ru Feng; An-Kang Li; Shi-Peng Sun; Xue-Li Cao (Desalination, 2024)

Vital residues-orientated rational design of butenolide inhibitors targeting Of ChtI - Qing Han; Yun-Jiang Zi; Tian-Yu Feng; Nan Wu; Ren-Xuan Zou; Jing-Yu Zhang; Ru-Lei Zhang; Qing Yang; Hong-Xia Duan (Medicinal Chemistry Research, 2024)

Ecological risk assessment of heavy metals in desulfurized seawater discharged from a coal-fired power plant in Qingdao - Yongliang Feng; Yiran Ru; Jun Wang; Xiaona Zhang; Hua Tian; Shuhe Lei; Ziang Zhao; Shaoguo Ru (Ecotoxicology, 2024)

Conductive nanofiltration membranes via in situ PEDOT-polymerization for electro-assisted membrane fouling mitigation - Tian-Zhi Jia; Ru Feng; Chun Cui; Qian Chen; Levente Cseri; Rong-Fei Zhou; Gyorgy Szekely; Xue-Li Cao; Shi-Peng Sun (Water Research, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Effect of high corn straw loads on short-chain fatty acid production in semi-continuous rumen reactor - Jinsong Liang; Panyue Zhang; Le Chen; Jianning Chang; Ru Zhang; Guangming Zhang; Yu Tian (Bioresource Technology, 2024)

Interacting with luteinizing hormone receptor provides a new elucidation of the mechanism of anti-androgenicity of bisphenol S - Xinda Zhang; Xiaorong Zhang; Yijiao Shi; Zhenzhong Zhang; Jun Wang; Shaoguo Ru; Hua Tian (Chemosphere, 2024)

Biological upcycling of nickel and sulfate as electrocatalyst from electroplating wastewater - Xian-Zhong Fu; Yu-Ru Yang; Tian Liu; Zhi-Yan Guo; Chen-Xuan Li; Hai-Yang Li; Kang-Ping Cui; Wen-Wei Li (Water Research, 2024)

Response of rumen microorganisms to pH during anaerobic hydrolysis and acidogenesis of lignocellulose biomass - Jinsong Liang; Panyue Zhang; Ru Zhang; Jianning Chang; Le Chen; Gongting Wang; Yu Tian; Guangming Zhang (Waste Management, 2024)

Advances in the study of silica nanoparticles in lung diseases - Li-Hong Ao; Yun-Geng Wei; Hong-Ru Tian; Hua Zhao; Jun Li; Jia-Qi Ban (Science of The Total Environment, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

A novel eco-friendly strategy for removing phenanthrene from groundwater: Synergism of nanobubbles and rhamnolipid - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Xueji You; Xin Ru Feng; Zhi Li; Lang Zhou; Yalei Zhang; Xiaoying Lai; Long Kahon; et al. (Science of The Total Environment, 2024)

Effect of marine heatwaves on juvenile greater amberjack (Seriola dumerili) - Yali Tian; Hang Li; Dongying Zhang; Chen Wang; Ruijuan Hao; Xiaoying Ru; Qin Hu; Yang Huang; Chunhua Zhu (Marine Environmental Research, 2024)

Corrigendum to “Silica nanoparticles promote oxLDL-induced macrophage lipid accumulation and apoptosis via endoplasmic reticulum stress signaling” [Sci. Total Environ., 631-632 (2018): 570-579] - Caixia Guo; Ru Ma; Xiaoying Liu; Tian Chen; Yang Li; Yang Yu; Junchao Duan; Xianqing Zhou; Yanbo Li; Zhiwei Sun (Science of The Total Environment, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Multipath charge transfer in Cu-BTC@CuS@CeO2 double p-n heterojunction hollow octahedrons for enhanced photocatalytic amine oxidation - Yaxin Ru; Yajie Chen; Xinyan Yu; Qiuyu Zhang; Yuejia Yin; Guohui Tian (Chemical Engineering Journal, 2023)

From air to airway: Dynamics and risk of inhalable bacteria in municipal solid waste treatment systems - Ru Fang; Tian Chen; Zhibang Han; Wenhui Ji; Yudan Bai; Zhipeng Zheng; Yinglong Su; Ling Jin; Bing Xie; Dong Wu (Journal of Hazardous Materials, 2023)

17β-Trenbolone activates androgen receptor, upregulates transforming growth factor beta/bone morphogenetic protein and Wnt signaling pathways, and induces masculinization of caudal and anal fins in female guppies (Poecilia reticulata) - Suqiu Zhang; Xinyu Li; Xuefu Li; Xue Wang; Shaoguo Ru; Hua Tian (Aquatic Toxicology, 2023)

Middle Triassic back-arc rifting in central China: Evidence from geochronology, geochemistry and Hf isotopes of basic–intermediate dykes in the Gonghe basin - Ru-Ye Tian; Lu Zeng; Jie Hui; Chen Ji; Kai-Jun Zhang (International Geology Review, 2023)

Permeability decides the effect of antibiotics on sedimentary nitrogen removal in Jiulong River Estuary - Ru Wan; Lianghao Ge; Bin Chen; Jin-Ming Tang; Ehui Tan; Wenbin Zou; Li Tian; Meng Li; Zongbao Liu; Lijun Hou; Guoyu Yin; Shuh-Ji Kao (Water Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

(±)-Sarcanan A, a pair of new enantiomeric dihydrobenzofuran neolignans from the aerial parts of Sarcandra glabra - Ju Liu; Qi-yin Wen; Hong-ru Tian; Bing-jin-feng Zhan; Long-ping Zhu; De-po Yang; Zhi-min Zhao (Natural Product Research, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Zebrafish (Danio rerio) TRβ- and TTR-based electrochemical biosensors: Construction and application for the evaluation of thyroid-disrupting activity of bisphenols - Yuejiao Li; Zhenzhong Zhang; Jun Wang; Yeqi Shan; Hua Tian; Pengfei Cui; Shaoguo Ru (Environmental Pollution, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Nonlocality of scale-dependent eddy mixing at the Kuroshio Extension - Mingyue Liu; Ru Chen; Wenting Guan; Hong Zhang; Tian Jing (Frontiers in Marine Science, 2023)
Although eddy parameterization schemes are often based on the local assumption, previous studies indicate that the nonlocality of total eddy mixing is prevalent at the Kuroshio Extension (KE). For eddy-permitting climate models, only mixing induced by eddies smaller than the resolvable scale of climate models ( L * ) needs to be parameterized. Therefore, here we aim to estimate and predict the nonlocality of scale-dependent eddy mixing at the KE region. We consider the separation scale L * ranging from 0.2 ∘ to 2.5 ∘ , which is comparable to the typical resolution of the ocean component of climate models. Using a submesoscale-permitting model solution (MITgcm llc4320) and Lagrangian particles, we estimate the scale-dependent mixing (SDM) nonlocality ellipses and then diagnose the square root of the ellipse area ( L n , p a r t i c l e ). L n , p a r t i c l e is a metric to quantify the degree of SDM nonlocality. We found that, for all the available L * values we consider, the SDM nonlocality is prevalent in the KE region, and mostly elevated values of L n , p a r t i c l e occur within the KE jet. As L * decreases from 2.5 ∘ to 0.2 ∘ , the ratio L n , p a r t i c l e / L * increases from 0.8 to 8.9. This result indicates that the SDM nonlocality is more non-negligible for smaller L * , which corresponds to climate models with relatively high resolution. As to the SDM nonlocality prediction, we found that compared to the conventional scaling and the curve-fitting methods, the random forest approach can better represent L n , p a r t i c l e , especially in the coastal regions and within the intense KE jet. The area of the Eulerian momentum ellipses well capture the spatial pattern, but not the magnitude, of L n , p a r t i c l e . Our efforts suggest that eddy parameterization schemes for eddy-permitting models may be improved by taking into account mixing nonlocality.

Soil erosion effectively alleviated by Miscanthus sacchariflorus, a potential candidate for land deterioration improvement - Chu Zhao; Yu-han Nie; Jian-pan Xin; Xiao-yu Zhu; Yan Li; Ru-nan Tian (Rhizosphere, 2023)

Chronology analysis of huge landslide based on ESR dating materials on sliding face in carbonate areas of south eastern Tibet - Chun-Ru Liu; Ying-Ying Tian; Hao Ji; Xi Ma; Chuan-Yi Wei; Jia-Xiang Dang; Gong-Ming Yin; Yong-Sheng Zhou; Ren-Mao Yuan (Quaternary Geochronology, 2023)

Multidimensional identification of single and regional meteorological drought considering flash‐season synthesis employed daily standardized effective precipitation and drought index in Guangxi, China - Yang Yun‐chuan; Yang Jia‐zhen; Tian Yi; Liao Li‐ping; Gan Ru‐min; Wang Wei‐quan; Wang Ting‐yan; Mo Chong‐xun; Li Xun‐gui; Sun Gui‐kai (International Journal of Climatology, 2023)
The frequent occurrence of extreme drought events in Guangxi has caused huge losses to human beings and economy in the region for many years. Therefore, this study adopted run theory and the objective identification method of regional extreme events (OITREE) and then carried out the comprehensive feature identification of multidimensional elements such as intensity, duration and area of meteorological drought events based on the daily standardized effective precipitation and drought index (SWAP) sequence of Guangxi from 1979 to 2018a. By comparing the evolutionary characteristics of drought elements identified by grid SWAP statistical analysis and OITREE, an integrated optimization scheme combining the accuracy of grid analysis and area identification is formed in this study. It was confirmed that the above two analysis methods had good correlation and consistency in revealing the evolution process of multidimensional elements of drought events. In terms of the frequency of drought events over a long period of time and the comprehensive characteristics of each element, the identification results of the OITREE method can better reveal the comprehensive characteristics of drought in Guangxi. Furthermore, the study found that flash droughts and seasonal droughts occurred alternately and were superimposed concurrently in Guangxi, and there were significant differences in the multidimensional spatial and temporal characteristics of these two types of droughts. Specifically, the frequency of flash drought was 1.60–4.00 times·(a) −1 , the duration varied from 20 to 60 days·(a) −1 and the concentration point of drought had a region‐wide dispersion; while the frequency of seasonal drought was 0.82–1.65 times·(a) −1 , the duration varied from 40–105 days·(a) −1 and the concentration point of drought had a local concentration. The research results can provide effective scientific support for operational drought refined forecast and early warning, and smart regulation of drought disaster risk.

The loss of Halloween gene function seriously affects the development and reproduction of Diaphorina citri (Hemiptera: Liviidae) and increases its susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Jing Wang; Tian-Rong Xin; Zhi-Wen Zou; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

Characteristics of dynamic shear modulus and damping ratio and the structural formula of EPS particles lightweight soil - Tian-shun Hou; Yi-xiang Cui; Xing-ru Pan; Ya-sheng Luo; Qian Liu (Soil Dynamics and Earthquake Engineering, 2023)

Extraction of weak hydrophobic sulforaphane from broccoli by salting-out assisted hydrophobic deep eutectic solvent extraction - Wen-wen Deng; Xue-ping Mei; Zi-jun Cheng; Tian-xiang gan; Xuan Tian; Jiang-nan Hu; Chuan-ru Zang; Bo Sun; Jing Wu; Yin Deng; Reza. A. Ghiladi; George H. Lorimer; et al. (Food Chemistry, 2023)

The preparation of Co/γ-Al2O3 and treatment of cartap pesticide wastewater by microwave catalytic oxidation - Jia Ru Dai; Kai Xuan Liu; Fang Lian; Xue Peng Tian; Yu Feng Zhang (Journal of Water Process Engineering, 2023)

An all-organic conditioning method to achieve deep dewatering of waste activated sludge and the underlying mechanism - Jie Li; Shaoqin Ru; Chenwei Yuan; Bo Wu; Yiwen Ji; Zijun Dai; Zhongfang Lei; Zhenya Zhang; Tian Yuan; Fengting Li; Misha Liu (Journal of Environmental Management, 2023)

Ultrastructure and distribution of antennal sensilla of Bombus terrestris (Hymenoptera: Apidae) - Xi Huang; Xi-lian Xu; Ru-xu Li; Su Wang; Li-xia Tian (Zoologischer Anzeiger, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Citric acid-based deep eutectic solvent (CA-DES) as a new soil detergent for the removal of cadmium from coking sites - Jie Qian; Ying-hua Li; Fei Su; Ji-guo Wu; Jia-ru Sun; Tian-ci Huang (Environmental Science and Pollution Research, 2023)

Soil moisture response to land use and topography across a semi-arid watershed: Implications for vegetation restoration on the Chinese Loess Plateau - Lu Xia; Ru-tian Bi; Xiao-yu Song; Wei Hu; Chun-juan Lyu; Xu Xi; Huai-you Li (Journal of Mountain Science, 2022)

Succinic acid inhibits photosynthesis of Microcystis aeruginosa via damaging PSII oxygen-evolving complex and reaction center - Yi-dong Chen; Yuan Zhu; Jian-pan Xin; Chu Zhao; Ru-nan Tian (Environmental Science and Pollution Research, 2021)

Effects of different pretreatment methods on biogas production and microbial community in anaerobic digestion of wheat straw - Ya-Ru Kang; Yao Su; Jing Wang; Yi-Xuan Chu; Guangming Tian; Ruo He (Environmental Science and Pollution Research, 2021)

LncRNA TUG1 exhibits pro-fibrosis activity in hypertrophic scar through TAK1/YAP/TAZ pathway via miR-27b-3p - Xian-Min Li; Wen-Yuan Yu; Qi Chen; Hui-Ru Zhuang; Su-Yue Gao; Tian-Lan Zhao (Molecular and Cellular Biochemistry, 2021)

Luteolin alleviates ulcerative colitis through SHP-1/STAT3 pathway - Bo-Lin Li; Dan-Yang Zhao; Peng-Li Du; Xiao-Tian Wang; Qian Yang; Yan-Ru Cai (Inflammation Research, 2021)

Cadmium phytotoxicity, related physiological changes in Pontederia cordata: antioxidative, osmoregulatory substances, phytochelatins, photosynthesis, and chlorophyll fluorescence - Jian-pan Xin; SiSi Ma; Chu Zhao; Yan Li; Ru-nan Tian (Environmental Science and Pollution Research, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Correction to: Micropropagation of tree peony (Paeonia sect. Moutan): A review - Shu-Sheng Wen; Lan Chen; Fang-Yun Cheng; Ru-Nan Tian (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Micropropagation of tree peony (Paeonia sect. Moutan): A review - Shu-Sheng Wen; Lan Chen; Ru-Nan Tian (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Effects of oxygen tension on the microbial community and functional gene expression of aerobic methane oxidation coupled to denitrification systems - Yi-Xuan Chu; Ruo-Chan Ma; Jing Wang; Jia-Tian Zhu; Ya-Ru Kang; Ruo He (Environmental Science and Pollution Research, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Removal of formaldehyde from the air with a suspended growth bioreactor - Ru Wang; Xuemei Li; Yong Feng; Faheem Tariq; Kunzhi Li; Yulin Wei; Jianhua Chen; Ciqing Jiang; Limei Tian; Yongqin Geng; Enming Miao; Chengming Zhang; et al. (International Journal of Environmental Research, 2019)

CBR-based integration of a hydrodynamic and water quality model and GIS—a case study of Chaohu City - Zhenliang Liao; Can Zhou; Wenchong Tian; Tiantian Hu; Ru Guo (Environmental Science and Pollution Research, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Genome-wide association study for flour color-related traits and polyphenol oxidase activity in common wheat - X.L. Jiang; G.F. Chen; X.J. Li; G. Li; Z.G. Ru; J.C. Tian (Cereal Research Communications, 2018)

Sexual characteristics of male guppies Poecilia reticulata serve as effect biomarkers of estrogens - Hua Tian; Yun Li; Wei Wang; Fei Zhao; Su Gao; Shaoguo Ru (Journal of Oceanology and Limnology, 2018)

The complete chloroplast genome sequence of the white strawberry Fragaria pentaphylla - Li-jun Bai; Yun-tian Ye; Qing Chen; Hao-ru Tang (Conservation Genetics Resources, 2017)

Calcium controls the formation of vacuoles from mitochondria to regulate microspore development in wheat - Dong Xiao Li; Hai Yan Hu; Gan Li; Zhen Gang Ru; Hui Qiao Tian (Plant Reproduction, 2017)

Genomewide association study for seeding emergence and tiller number using SNP markers in an elite winter wheat population - GUANG FENG CHEN; RU GANG WU; DONG MEI LI; HAI XIA YU; ZHIYING DENG; JI CHUN TIAN (Journal of Genetics, 2017)

Arabidopsis heat stress transcription factors A2 (HSFA2) and A3 (HSFA3) function in the same heat regulation pathway - Xiao-dong Li; Xiao-li Wang; Yi-Ming Cai; Jia-hai Wu; Ben-tian Mo; Er-ru Yu (Acta Physiologiae Plantarum, 2017)

Inhibition of the Receptor for Advanced Glycation End-Products (RAGE) Attenuates Neuroinflammation While Sensitizing Cortical Neurons Towards Death in Experimental Subarachnoid Hemorrhage - Hua Li; Jia-Sheng Yu; Ding-Ding Zhang; Yi-Qing Yang; Li-Tian Huang; Zhuang Yu; Ru-Dong Chen; Hong-Kuan Yang; Chun-Hua Hang (Molecular Neurobiology, 2017)

A genome-wide analysis of the ASYMMETRIC LEAVES2/LATERAL ORGAN BOUNDARIES (AS2/LOB) gene family in barley (Hordeum vulgare L.) - Bao-jian Guo; Jun Wang; Shen Lin; Zheng Tian; Kai Zhou; Hai-ye Luan; Chao Lyu; Xin-zhong Zhang; Ru-gen Xu (Journal of Zhejiang University-SCIENCE B, 2016)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

Identification of geranylgeranyl diphosphate synthase genes from Tripterygium wilfordii - Meng Zhang; Ping Su; Yong-Jin Zhou; Xiu-Juan Wang; Yu-Jun Zhao; Yu-Jia Liu; Yu-Ru Tong; Tian-Yuan Hu; Lu-Qi Huang; Wei Gao (Plant Cell Reports, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Model-based meta-analysis of the effects of non-selective and α1-selective GABAA receptor agonists in healthy volunteers - Yu-Peng Ren; Ru-Jia Xie; Scott Marshall; Liang Li; Tian-Yan Zhou; Wei Lu (European Journal of Clinical Pharmacology, 2015)

Induction of DNA base damage and strand breaks in peripheral erythrocytes and the underlying mechanism in goldfish (Carassius auratus) exposed to monocrotophos - Fei Zhao; Bai Wang; Xiaona Zhang; Hua Tian; Wei Wang; Shaoguo Ru (Fish Physiology and Biochemistry, 2015)

Gene order rearrangement of the M gene in the rabies virus leads to slower replication - Xian-Feng Yang; Jiao-Jiao Peng; Hong-Ru Liang; You-Tian Yang; Yi-Fei Wang; Xiao-Wei Wu; Jiao-Jiao Pan; Yong-Wen Luo; Xiao-Feng Guo (VirusDisease, 2014)

An Emerging Water Contaminant, Semicarbazide, Exerts an Anti-estrogenic Effect in Zebrafish (Danio rerio) - Su Gao; Wei Wang; Hua Tian; Xiaona Zhang; Linlin Guo; Shaoguo Ru (Bulletin of Environmental Contamination and Toxicology, 2014)

Seasonal variations of monocarbonyl and dicarbonyl in urban and sub-urban sites of Xi’an, China - K. F. Ho; Steven Sai Hang Ho; W. T. Dai; J. J. Cao; Ru-Jin Huang; Linwei Tian; W. J. Deng (Environmental Monitoring and Assessment, 2014)

Assessment of Recanalization of Chronic Total Occlusions on Left Ventricular Function in Patients With or Without Previous Myocardial Infarction by Real-time Three-Dimensional Echocardiography - Wen-Wei Yue; Feng-Tian Huangfu; Jie Yin; Tao Wang; Guang-Fu Wang; Ru-Yi Jia (Cell Biochemistry and Biophysics, 2012)

Expression of tyrosine kinase receptor C in the segments of the spinal cord and the cerebral cortex after cord transection in adult rats - Dong-Xiang Qian; Hong-Tian Zhang; Ying-Qian Cai; Peng Luo; Ru-Xiang Xu (Neuroscience Bulletin, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Characterization of human embryonic stem cell-derived hematopoietic progenitor phenotype - Hai-Yang Zhou; Xiao-Yi Yang; Li-Jian Tao; Yue-Tian Chang; Ru-Ping Dai (In Vitro Cellular & Developmental Biology - Animal, 2010)

Differentiation of cryopreserved human umbilical cord blood-derived stromal cells into cells with an oligodendrocyte phenotype - Yong-Chun Luo; Hong-Tian Zhang; Hao-Yu Cheng; Zhi-Jun Yang; Yi-Wu Dai; Ru-Xiang Xu (In Vitro Cellular & Developmental Biology - Animal, 2010)

cDNA, genomic sequence cloning and overexpression of ribosomal protein S25 gene (RPS25) from the Giant Panda - Yan-zhe Hao; Wan-ru Hou; Yi-ling Hou; Yu-jie Du; Tian Zhang; Zheng-song Peng (Molecular Biology Reports, 2009)

Induced hydrolytic enzymes of ectomycorrhizal fungi against pathogen Rhizoctonia solani - Ming Tang; Ru-Qin Zhang; Hui Chen; Hai-Han Zhang; Zhi-Qiang Tian (Biotechnology Letters, 2008)

Androgen receptor: a new player associated with apoptosis and proliferation of pancreatic beta-cell in type 1 diabetes mellitus - Ru-Jiang Li; Shu-Dong Qiu; Hai-Xu Wang; Hong Tian; Li-Rong Wang; Yong-Wei Huo (Apoptosis, 2008)

Phosphorus fractions and adsorption characteristics of floodplain sediments in the lower reaches of the Hanjiang River, China - Jian-ru Tian; Pei-jiang Zhou (Environmental Monitoring and Assessment, 2008)

Three dimensional kinematics of rapid compensatory eye movements in humans with unilateral vestibular deafferentation - Jun-Ru Tian; Benjamin T. Crane; Akira Ishiyama; Joseph L. Demer (Experimental Brain Research, 2007)

Effect of Pyrogallol on the Growth and Pigment Content of Cyanobacteria-Blooming Toxic and Nontoxic Microcystis Aeruginosa - Bi-Yun Liu; Pei-Jiang Zhou; Jian-Ru Tian; Shun-Yao Jiang (Bulletin of Environmental Contamination and Toxicology, 2007)

Temporal dynamics of semicircular canal and otolith function following acute unilateral vestibular deafferentation in humans - Jun-ru Tian; Akira Ishiyama; Joseph L. Demer (Experimental Brain Research, 2007)

Effect of unilateral vestibular deafferentation on the initial human vestibulo-ocular reflex to surge translation - Jun-Ru Tian; Akira Ishiyama; Joseph L. Demer (Experimental Brain Research, 2007)

Initiation and cancellation of the human heave linear vestibulo-ocular reflex after unilateral vestibular deafferentation - Benjamin T. Crane; Jun-Ru Tian; Akira Ishiyama; Joseph L. Demer (Experimental Brain Research, 2005)

Vestibular catch-up saccades augmenting the human transient heave linear vestibulo-ocular reflex - Jun-ru Tian; BenjaminT. Crane; JosephL. Demer (Experimental Brain Research, 2003)

Effect of aging on the human initial interaural linear vestibulo-ocular reflex - Jun-Ru Tian; Benjamin T. Crane; Gerald Wiest; Joseph L. Demer (Experimental Brain Research, 2002)

Dynamic visual acuity during passive and self-generated transient head rotation in normal and unilaterally vestibulopathic humans - Jun-ru Tian; Igor Shubayev; Joseph Demer (Experimental Brain Research, 2002)

Seasonal dynamics of coastal ecosystems and export production at high latitudes: A modeling study - Ru Cheng Tian; Alain F. Vézina; Michel Starr; François Saucier (Limnology and Oceanography, 2001)
Export of organic matter from the surface to deeper waters often shows much smaller seasonal variations than primary production or nitrate‐based new production in mid‐ to high‐latitude marine systems. The mechanisms underlying this pattern remain poorly understood, but seasonal shifts in food web structure and dynamics have been implicated. We report here on an ecosystem modeling analysis of a high‐resolution (biweekly) time series of biomass, production, and export flux (sediment trap) measurements conducted in 1991 in Bonne Bay (Newfoundland). This time series shows the classical pattern of a spring bloom followed by a summer low biomass period, yet export is bimodal, with maxima during spring and late summer. The ecosystem model was forced by diagnostic vertical mixing calculations based on temperature and salinity records taken every 3 d and hourly wind data. The physical analysis indicated that the nitrate flux into the euphotic zone during summer was equivalent to that during the spring and fall seasons and accounted for half of the summer export. Statistical adjustments of the parameters of the ecosystem model indicated that strong production of dissolved organic carbon during the spring bloom, high temperature dependence of microbial activity, and physico‐chemical particle aggregation played key roles in explaining the remainder of the summer export. Seasonal changes in trophic pathways between spring and summer, such as a shift from a herbivorous to a microbial food web, played a comparatively smaller role. Our modeling analysis suggests that physical mixing processes and physico‐chemical aggregation processes are at least as important as shifts in food web trophic pathways in explaining the postbloom export flux in mid‐ to high‐latitude marine systems.

Impairments in the initial horizontal vestibulo-ocular reflex of older humans - Jun-Ru Tian; Robert W. Baloh; Igor Shubayev; Joseph L. Demer (Experimental Brain Research, 2001)

Dynamic visual acuity during transient and sinusoidal yaw rotation in normal and unilaterally vestibulopathic humans - Jun-ru Tian; Igor Shubayev; Joseph L. Demer (Experimental Brain Research, 2001)

Vestibular catch-up saccades in labyrinthine deficiency - Jun-ru Tian; Benjamin T. Crane; Joseph L. Demer (Experimental Brain Research, 2000)

Initial vestibulo-ocular reflex during transient angular and linear acceleration in human cerebellar dysfunction - Benjamin T. Crane; Jun-Ru Tian; Joseph L. Demer (Experimental Brain Research, 2000)